A Study on Cellulose Fiber Modified Stone Matrix Asphalt and Conventional Stone Matrix Asphalt (International Journal of Innovative Research in Engineering & Management, 2023)
Stone Matrix Asphalt (SMA) is a breach  separated bitumen combination. It is essential for the  mixture that the coarse aggregates have direct stone-on stone contact with each other. This is one of the  requirements for the mixture. In the present investigation,  SMA mixes with two different aggregate gradations and  two different nominal maximum aggregate sizes, 16mm  and 13.2mm, were created. These mixtures were given the  designations SMA 1 and SMA 2, respectively. Three  different types of fibers, including pelletized Cellulose  Fiber (CF), Coconut Coir (CC), and Sisal Fiber (SF), and  Shredded Waste Plastics (SWP) were used in mixtures  with VG 30 bitumen to control drain down According to  the findings of the drain down test, the amount of fiber that  could be included in the mixture was capped at 0.3% by  weight, while the percentage of SWP that may be included  was between 4% and 16% by weight of bitumen. When  case SWP combinations were tested, it was found that 8  and 12% plastic percentage generated the best results. The  SMA 1 gradation exhibited superior outcomes than the  SMA 2 gradation for all sorts of mixtures, with the  exception of moisture susceptibility, where both gradations  performed virtually identically.
Keywords: Stone Matrix Asphalt; stone to stone contact; drain down; fiber additives; modified bitumen; Shredded Waste Plastic